Innovative Service Quality Boosts Patient Satisfaction: Kualitas Layanan yang Inovatif Meningkatkan Kepuasan Pasien - Firdaus, Muhammad Zaqqi Zamroni; Cahyana , Atikha Sidhi (Indonesian Journal of Innovation Studies, 2024)
This study examines factors affecting service quality, patient satisfaction, and loyalty at Puskesmas XYZ, using Structural Equation Modeling (SEM) on data from 108 respondents. The results pinpoint doctor-patient interaction as crucial for service quality (loading factor 0.732), satisfaction (0.692), and loyalty (0.758). Suggestions include improving queue management, proposing a web-based system for efficiency. Future research can expand service quality variables for broader impact assessment. Highlight: Key Findings: Doctor interaction highly impacts patient loyalty and satisfaction. Recommendation: Implement web-based queue management for improved healthcare service. Future Research: Expand service quality variables for a broader patient assessment. Keyword: Service Quality, Patient Satisfaction, Loyalty, Structural Equation Modeling (SEM), Queue Management